2022
DOI: 10.3389/fmed.2022.905978
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate as a Potential Beneficial Anion in Resuscitation Fluids

Abstract: There have been ongoing debates about resuscitation fluids because each of the current fluids has its own disadvantages. The debates essentially reflect an embarrassing clinical status quo that all fluids are not quite ideal in most clinical settings. Therefore, a novel fluid that overcomes the limitations of most fluids is necessary for most patients, particularly diabetic and older patients. Pyruvate is a natural potent antioxidant/nitrosative and anti-inflammatory agent. Exogenous pyruvate as an alkalizer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 106 publications
(157 reference statements)
0
18
0
Order By: Relevance
“…Furthermore, a continuous infusion of IV pyruvate (0.1 mmol/kg/min for 6 h) during the extracorporeal membrane oxygenation (ECMO) protocol in an immature swine model confirmed that it enhanced anaplerotic flux (replenishment of tricarboxylic acid (TCA)-cycle substrates) through pyruvate carboxylation and activated fatty acid oxidation, improving mitochondrial nutrients and energy metabolisms in the immature myocardium under conditions emulating ventricular unloading during ECMO (Ledee et al, 2015). Therefore, these extremely high concentrations (2.0 M) and large doses of pyruvate infusion had been known as optimal in preclinical studies and clinical trials (Sharma et al, 2015;Zhou, 2022). Moreover, as an EP alleviation of acute pancreatitis in many studies, a high dose of IV SP (0.25 mg/kg/h for 4 h) infusion vs. NS verified its protection against cerulein-induced acute pancreatitis with a decline of hyperamylasemia and alleviation of histopathological changes in rats (Ziolkowski et al, 2008).…”
Section: Intravenous Pyruvate-based Fluids In Shock Resuscitationmentioning
confidence: 96%
See 4 more Smart Citations
“…Furthermore, a continuous infusion of IV pyruvate (0.1 mmol/kg/min for 6 h) during the extracorporeal membrane oxygenation (ECMO) protocol in an immature swine model confirmed that it enhanced anaplerotic flux (replenishment of tricarboxylic acid (TCA)-cycle substrates) through pyruvate carboxylation and activated fatty acid oxidation, improving mitochondrial nutrients and energy metabolisms in the immature myocardium under conditions emulating ventricular unloading during ECMO (Ledee et al, 2015). Therefore, these extremely high concentrations (2.0 M) and large doses of pyruvate infusion had been known as optimal in preclinical studies and clinical trials (Sharma et al, 2015;Zhou, 2022). Moreover, as an EP alleviation of acute pancreatitis in many studies, a high dose of IV SP (0.25 mg/kg/h for 4 h) infusion vs. NS verified its protection against cerulein-induced acute pancreatitis with a decline of hyperamylasemia and alleviation of histopathological changes in rats (Ziolkowski et al, 2008).…”
Section: Intravenous Pyruvate-based Fluids In Shock Resuscitationmentioning
confidence: 96%
“…Furthermore, a high concentration of IV pyruvate (0.1 mmol/kg/min for over 60 min) evidenced its preservation of antiglycation defenses in cerebral protection after cardiac arrest in pigs (Scott et al, 2017). Pyruvate action as an inhibitor of methylglyoxal-induced advanced glycation end products (AGEs), which are one of the triggers in many organ complications of critical illnesses, was subsequently shown in exogenous pyruvate protection against diabetic cataract and diabetic nephropathy (Zhou, 2022). In another study of porcine cardiac arrest with a large dose of IV pyruvate (2.0 M, 0.1 mmol/kg/min for over 60 min with a plasma pyruvate level 4-5 mM), it is worth noting that despite the occurrence of transient hypernatremia after pyruvate infusion, higher blood potassium levels were rapidly maintained close to normal ranges in contrast to NS or 10% NaCl infusion apart from systemic hemodynamics and cerebral function improvements and acidosis correction (Mongan et al, 1999;Cherry et al, 2015).…”
Section: Intravenous Pyruvate-based Fluids In Shock Resuscitationmentioning
confidence: 99%
See 3 more Smart Citations